Integrating Artificial Intelligence with 3D Printing Technology in Healthcare: Sustainable Solutions for Clinical Training Optimization - Ikhsan, Ramzi Zainum; Rahayu, Sri; Arribathi, Abdul Hamid; Azizah, Nur (ADI Publisher, 2025)
Integrating Artificial Intelligence (AI) with 3D printing technology offers transformative solutions in healthcare, specifically improving clinical training through precise and customizable replicas of human anatomy. Traditional training methods face challenges such as limited access to high quality models, lack of precision, adaptability, and the environmental impact of resource use. This study employed a mixed methods approach, combining quantitative analysis of model accuracy and input from healthcare professionals, to evaluate the effectiveness of AI optimized 3D printing. The focus was on AI enhanced 3D printing models designed for healthcare training. Traditional methods often lack precision, adaptability, and scalability, limiting their effectiveness in dynamic healthcare scenarios. AI based 3D printing reduces material use by 30% while providing high quality, customized training models, improving accessibility and sustainability. This research highlights the potential of AI and 3D printing integration to drive technological innovation, align healthcare training with Sustainable Development Goals (SDGs), and promote a more sustainable and efficient future in medical education.